Complexity analysis of heart sounds - Cheong, Pei San (2017)
Phonocardiography (PCG) is the digital way of representing heart sound where it possesses many characteristics that can point to the cardiac disease the person suffering from. An initial step to analyze heart sounds is to determine whether it is abnormal or not. One of the efficient way is to analyze them using complexity of the signal by estimating and exploring for characteristics of the disease. The project involves detecting cardiac abnormality in a PCG using complexity analysis via MATLAB software to define appropriate complexities parameters for extraction, and classification of the heart sounds. This paper presents the study of the analysis with detailed description of the classification procedures. The simulation results achieved over the span of 2 semesters had met the intended outcome which highlighted the feasibility and validity of the developed measures.